Comparación de sistemas de cálculo de dosis para tratamientos con placas COMS - Aranda-González, Kenia (My University, 2026)
La braquiterapia ocular con placas COMS permite tratar melanomas y tumores intraoculares con alta precisión, administrando dosis elevadas al tumor mientras se protegen estructuras críticas del ojo. Este trabajo desarrolla y valida una herramienta de cálculo dosimétrico en Python, basada en los formalismos TG-43 y TG-129, que calcula de forma transparente la dosis en distintos puntos del ojo en condiciones homogéneas y heterogéneas. Validada frente al software clínico Plaque Simulator, la herramienta muestra una alta concordancia, con errores generalmente inferiores al 5 % y dentro de los márgenes aceptados. Además de servir como método de verificación dosimétrica, facilita comprender el impacto de los parámetros físicos en la distribución de dosis, aportando un recurso práctico y fiable en braquiterapia ocular.
Ocular brachytherapy using COMS plaques is a highly precise treatment for uveal melanoma and other intraocular tumors, delivering high doses to the tumor while sparing critical ocular structures. This work presents the development and validation of an independent dosimetric calculation tool in Python, based on the AAPM TG-43 and TG-129 formalisms, allowing transparent and clear dose calculations at various ocular points under both homogeneous and heterogeneous conditions. The tool was validated against the clinical software Plaque Simulator, showing high agreement with relative errors generally below 5% and within accepted clinical margins. In addition to serving as an independent dose verification method, this development enhances the understanding of physical parameters affecting dose distribution, establishing a practical and reliable resource for dosimetric verification in ocular brachytherapy with COMS plaques in routine clinical practice.
Keywords: braquiterapia; COMS; placas COMS; melanoma ocular; cálculo redundante; brachytherapy; COMS plaques; Ocular melanoma; redundant calculation; Grado en Física